Tipologia de áreas úmidas urbanas em parques municipais de Belo Horizonte/MG - Luisa Lima Borges Ferreira (2020)
Wetlands such as swamps, bogs, mangroves, marshes and diffuse springs are complex environmental systems periodically or permanently flooded. These systems provide many ecosystem services, for example peak flood reduction, aquifer recharge and reduction of runoff speed. However Brazilian laws do not adequately cover nor set measures for the management and protection of wetlands, especially in the urban context. With the lack of knowledge regarding urban wetlands and the scarce research in the field, the development of studies becomes evermore necessary for the protection and management of these systems. This dissertation aims to elaborate a framework for the study of wetlands in urban areas in Bazil through the diagnosis and case study on urban wetlands present in the city of Belo Horizonte in terms of environmental features, seeking to develop a typological classification system. Typological classification is an important tool to understand and learn the local environmental setting, to detect fragilities and to allocate adequate policies. As specific objectives we have: identifying and analyzing physiographic patterns of features; determining the impacts and pressures coming from anthropic action; defining the criteria for classification of wetlands; and contributing for studies on urban wetlands in Brazil. This research was structured in office, in field and in laboratory. Initially literature research was conducted on urban wetlands and on the history of Belo Horizonte’s water resources. Then the areas to be investigated were selected through secondary data and the field work was structured, seeking to include the whole of the municipality. 35 urban wetlands were studied and characterized in 15 municipal parks in seven regional units of the city during February and August 2019. The information on wetlands was gathered through checklists, the areas were georeferenced and water and soil materials were collected for analysis in the lab. The water and soil analysis sought to detect organic water pollution and to characterize the soils. The typology was developed through cluster analysis through the software R. Field and laboratory data were treated and organized in a database for the statistical procedure, which was tested using many methods and distances. The Ward method using binary distance was selected and the number of clusters was determined using NbClust algorithm. The typology presents four types of wetlands that represent part of the physical-environmental reality of urban wetlands in Belo Horizonte. Maps and visual charts were made to synthesize the information on each studied wetland. With this dissertation we hope to contribute to knowledge on urban wetlands of Belo Horizonte in order to subsidize strategies for protection and management of these systems. With this work we expect to assist the understanding of the theme and to draw attention to the study and conservation of wetlands in the urban context, especially regarding their status of ecosystem services providers.